Diverse climate sensitivities in Picea crassifolia and Juniperus przewalskii promote different responses to climate warming in Qilian Mountains, northwest China. Issue 1 (2nd January 2021) - Ran, Yilin; Zhang, Lingnan; Wang, Rui; Zhao, Shoudong; Liu, Xiaohong
ABSTRACT: The effects of climate warming are widely recognized; however, some studies have suggested that the rate of warming has slowed since the end of the twentieth century. However, the relationships between climate and the radial growth of trees during different periods of climate change have yet to be investigated fully. In the present study, tree-ring core samples were collected from Picea crassifolia and Juniperus przewalskii in the Qilian Mountains of northwest China to study the relationships between climate and radial growth. The core samples were divided into two groups: one with significant tree-growth reduction and another with insignificant reduction. Trees showing with significant growth reduction were more sensitive to climate change than trees showing insignificant growth reduction during the period of climate warming. P. crassifolia exhibited a stronger response to precipitation during May–June of the current year and from August of the previous year to June of the current year, both before and after climate warming. P. crassifolia exhibited a positive coherence with precipitation from August–September of the previous year and a negative coherence with the temperature of the current June during climate warming. After climate warming, J. przewalskii responded positively to precipitation in the current May and from the previous August to the current May. J. przewalskii also responded positively to temperature during January–February of the current year after warming. P. crassifolia responded to precipitation more strongly than J. przewalskii, whereas J. przewalskii showed a closer relationship to temperature than P. crassifolia .